Quantification of Huntington’s Disease Related Markers in the R6/2 Mouse Model - Etxeberria-Rekalde, Estibaliz; Alzola-Aldamizetxebarria, Saioa; Flunkert, Stefanie; Hable, Isabella; Daurer, Magdalena; Neddens, Joerg; Hutter-Paier, Birgit (Frontiers in Molecular Neuroscience, 2021)
Huntington’s disease (HD) is caused by an expansion of CAG triplets in the huntingtin gene, leading to severe neuropathological changes that result in a devasting and lethal phenotype. Neurodegeneration in HD begins in the striatum and spreads to other brain regions such as cortex and hippocampus, causing motor and cognitive dysfunctions. To understand the signaling pathways involved in HD, animal models that mimic the human pathology are used. The R6/2 mouse as model of HD was already shown to present major neuropathological changes in the caudate putamen and other brain regions, but recently established biomarkers in HD patients were yet not analyzed in these mice. We therefore performed an in-depth analysis of R6/2 mice to establish new and highly translational readouts focusing on Ctip2 as biological marker for motor system-related neurons and translocator protein (TSPO) as a promising readout for early neuroinflammation. Our results validate already shown pathologies like mutant huntingtin aggregates, ubiquitination, and brain atrophy, but also provide evidence for decreased tyrosine hydroxylase and Ctip2 levels as indicators of a disturbed motor system, while vesicular acetyl choline transporter levels as marker for the cholinergic system barely change. Additionally, increased astrocytosis and activated microglia were observed by GFAP, Iba1 and TSPO labeling, illustrating, that TSPO is a more sensitive marker for early neuroinflammation compared to GFAP and Iba1. Our results thus demonstrate a high sensitivity and translational value of Ctip2 and TSPO as new marker for the preclinical evaluation of new compounds in the R6/2 mouse model of HD.